Are urban residents seeking appropriate care for malaria? evidence from an exploratory qualitative study in two cities in nigeria - Akintayo Ogunwale; IkeOluwapo Ajayi; Eniola Bamgboye; Al-Mukhtar Adamu; Musa Bello; Morenikeji Olawuwo; Adeniyi Fagbamigbe; Joshua Akinyemi; Ifeoma Ozodiegwu (BMC Health Services Research)
Abstract Background Unplanned and rapid urbanization within Nigerian cities with the attendant environmental consequences may hinder achieving malaria elimination goal. Presently, there are limited qualitative studies on malaria case management and care-seeking patterns by settlement type in urban areas in Nigeria. This study, investigated malaria-related health seeking behaviours among different settlement types in Ibadan and Kano metropolises, Nigeria. Methods This qualitative study involved conduct of nine Focus Group Discussions (FGDs) sessions among community members and 20 Key Informant interviews (KIIs) with healthcare providers and community stakeholders in each metropolis. Participants were purposively drawn from three settlement types – formal, informal and urban slum. Pretested FGD and KII guides were used to collect data. Data were subjected to thematic content analysis. Results Government-owned health facilities especially Primary Health Care (PHC) facilities was a major place identified as where many community members prefer to seek care for suspected malaria infection. Reasons adduced included proximity of facilities and services affordability. A common viewpoint was that most community members in informal and slum communities in both metropolises often patronize Proprietary Patent Medicine Vendors (PPMVs) or drug sellers as the first point for treatment of suspected malaria infection. Adduced reasons included poverty and non-availability of 24 h services in PHC facilities. High cost of treatment, poor attitude of health workers, long waiting time and cultural beliefs were identified as key factors influencing community members’ decision not to seek care in health facilities. It was noted that the rich prefer to seek treatment in private hospitals, while the poor usually visit PHCs or resort to other options like buying drugs from PPMVs or use herbal drugs. Conclusion The standard practice of seeking care in health facilities was influenced by diverse factors including treatment cost, health workers’ attitude and waiting time in health facilities. A commoner practice of seeking care from patent medicine vendors and herbal drug sellers among informal settlements and slums dwellers calls for public health interventions. Specifically, the provision of free or affordable malaria care in health facilities and patient-friendly environments; and training of non-formal care providers on appropriate malaria care and referral to health facilities are recommended.